Pengaruh Manajemen Sumber Daya Manusia Terhadap Kualitas Pelayanan Pada Gereja Bukit Zaitun Malanu Kota Sorong - Andreas Iyai; Philipus Sinay; Andrei Maryen; Edward Clan (Journal on Education, 2023)
Where there is no influence of Human Resource Management on the Quality of Service at the Bukit Olive Church, Malanu, Sorong City, the church dies, so the need for quality management provides an understanding that church management is very necessary for the church to run the service and carry out God's great commission. This research methodology uses quantitative approach. Data obtained in the field is in the form of quantitative data, according to Sugiyono, is data that is processed from research results in the form of numbers, where the quantitative approach is the acquisition of data from various sources of information that are relevant to the problem being studied. The aim of service quality is a form of public assessment of the level of service provided. receive the expected level of service. Human resources are the only resources that have feelings, desires, skills, knowledge, encouragement, power and work.